2021
DOI: 10.3390/atmos12111409
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Study on Medium-Scale Traveling Ionospheric Disturbances Observed over the South American Equatorial Region

Abstract: Using data collected by the GNSS dual-frequency receivers network, de-trended TEC maps were generated to identify and characterize the medium-scale traveling ionospheric disturbances (MSTIDs) over the South American equatorial region (latitude: 0∘ to 15∘ S and longitude: 30∘ to 55∘ W) during solar cycle 24 (from January 2014 to December 2019). A total of 712 MSTIDs were observed during quiet geomagnetic conditions. The Frequency of occurrence of MSTID is high during the solar maximum and low in the minimum pha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
14
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 65 publications
(133 reference statements)
5
14
1
Order By: Relevance
“…They reported an increase in amplitude with an increase in solar activity, and that the amplitude tends to increase with increasing auroral electrojet (AE) index, and also found that MSTIDs amplitude is dominantly high at daytime. The increasing MSTIDs with increase in solar activity in the current result also agrees with Essien et al (2021) where they reported a long-term study of MSTIDs occurrence rate during 2014-2019 over South American equatorial region (Lat: 0°-15°S and Long: 30°-55°W). They concluded that MSTIDs increases with increasing solar activity.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…They reported an increase in amplitude with an increase in solar activity, and that the amplitude tends to increase with increasing auroral electrojet (AE) index, and also found that MSTIDs amplitude is dominantly high at daytime. The increasing MSTIDs with increase in solar activity in the current result also agrees with Essien et al (2021) where they reported a long-term study of MSTIDs occurrence rate during 2014-2019 over South American equatorial region (Lat: 0°-15°S and Long: 30°-55°W). They concluded that MSTIDs increases with increasing solar activity.…”
Section: Discussionsupporting
confidence: 91%
“…However, the nighttime MSTIDs exhibited highest occurrence rate observed in June solstice during * 2100-0200 LT and * 1900-0200 LT at northwest and northeast, respectively. In the current study, the magnitude of MSTIDs generally increases with increase in solar activity (Essien et al, 2021;Oinats et al, 2016). Our MSTIDs seasonal occurrence results show a larger part of agreement with the MSTIDs investigation conducted by Tsugawa et al (2006) who reported MSTIDs occurrence over South-East Asian sector (Japan).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Theoretically, this phenomenon was first investigated in the 1960s by the pioneering work of Hines (1960), although the first observation of the wavelike disturbances was in the 1940s (Munro, 1948). In the last 10 years, dozens of theoretical and observational studies in different geographic regions have been carried out using diverse instruments, such as ionosondes (e.g., Amorim et al., 2011; Sherstyukov et al., 2018), satellites (e.g., Bolmgren et al., 2020), incoherent scatter radars (e.g., Negale et al., 2018; Nicolls et al., 2010, 2014; Vadas & Nicolls, 2009), and all‐sky airglow imagers (e.g., Figueiredo et al., 2018b; Martinis et al., 2019; Paulino et al., 2016; Smith et al., 2013; Terra et al., 2020), total electron content (e.g., Azeem et al., 2015, 2017; Chen et al., 2019; Essien et al., 2021, 2022; Figueiredo et al., 2018a; Sivakandan et al., 2021), and Doppler radar sounder (Crowley & Rodrigues, 2012; Vadas & Crowley, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In the middle latitudes, day-and nighttime MSTIDs have been reported to be generated via atmospheric gravity waves propagating in the F-layer bottom height [10][11][12][13] and Perkins instability [14][15][16], while at high latitudes, MSTIDs have been attributed to the geomagnetic storms and polar electroject [17]. Several authors have suggested that the possible source regions for equatorial and low-latitude MSTIDs, especially those propagating southeastward, are linked to the gravity waves in the thermosphere that originate from the ITCZ [10,[18][19][20]. Knowing and understanding the sources of MSTIDs is of utmost importance for unraveling the complexities of the neutral atmosphere and ionosphere coupling and, eventually, the prediction of the climatology of the occurrence of MSTIDs in the future.…”
Section: Introductionmentioning
confidence: 99%